2014
DOI: 10.3164/jcbn.13-107
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of radical scavenging properties of shikonin

Abstract: With the aim of developing effective anti-inflammatory drugs, we have been investigating the biochemical effects of shikonin of “Shikon” roots, which is a naphthoquinone with anti-inflammatory and antioxidative properties. Shikonin scavenged reactive oxygen species like hydroxyl radical, superoxide anion (O2•−) and singlet oxygen in previous studies, but its reactivity with reactive oxygen species is not completely understood, and comparison with standard antioxidants is lacking. This study aimed elucidation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…As we ( 16 ) and others ( 14 , 15 ) have previously reported, shikonin scavenges O 2 •− , with IC 50 values of 2.9~17 µM depending on the source, assay conditions and O 2 •− detection system used. To know the contribution of the chemical scavenging of O 2 •− by shikonin in RH buffer with 1 µM CLA used in assays with cells, we first investigated the quenching of O 2 •− -produced chemiluminescence of the hypoxanthine-xanthine oxidase reaction ( 3 ) in the CFL-C2000 (Fig.…”
Section: Resultsmentioning
confidence: 59%
See 4 more Smart Citations
“…As we ( 16 ) and others ( 14 , 15 ) have previously reported, shikonin scavenges O 2 •− , with IC 50 values of 2.9~17 µM depending on the source, assay conditions and O 2 •− detection system used. To know the contribution of the chemical scavenging of O 2 •− by shikonin in RH buffer with 1 µM CLA used in assays with cells, we first investigated the quenching of O 2 •− -produced chemiluminescence of the hypoxanthine-xanthine oxidase reaction ( 3 ) in the CFL-C2000 (Fig.…”
Section: Resultsmentioning
confidence: 59%
“…Previous studies have indicated that shikonin chemically scavenges ROS such as O 2 •− ( 14 16 ) and hydroxyl radical, ( 15 , 17 ) and biologically behaves as an anti-inflammatory compound by directly targeting these oxidative molecules. The effects of shikonin on gene expression of key molecules involved in the inflammatory response have also been described; ( 11 , 13 ) however, the mechanisms of how shikonin suppresses O 2 •− generation of cells remained unclear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations